A Molecular Docking Study: Targetting HIV-1 Integrase Protein Against Selected Phytocompounds from Calophyllum Lanigerum - Rishabh Kulkarni; Shubham Wanarase (International Journal of Molecular Biotechnological Research, 2023)
Objectives: The most common form of HIV that causes AIDS is HIV-1. The World Health Organization has estimated roughly 75 million plus HIV-1 infections till date and roughly 40 million deaths (as of 2021). Thus, this study was done to identify natural compounds from Calophyllum lanigerum, a medicinal plant largely endemic to South-East Asia, to inhibit the spread of this disease. It did so by using molecular docking methods, Lipinski drug-likeness prediction, and the ADME analysis. Methods: The Protein Data Bank database was used to retrieve the HIV-1 Integrase protein (core domain with catalytic activity). The ligands were obtained from PubChem. PyRx was used for the docking analysis, and Biovia Discovery Studio Visualizer was used to display the receptor ligand interactions. Swiss-ADME, an online tool, was used to conduct the ADMET and Lipinski drug-likeliness study. Results: Five compounds from C. lanigerum have been identified by molecular docking studies as having potential binding affinity to prevent the integration of HIV-1 dsDNA (reverse transcribed) into the genome of human immunocytes, such as CD4+ T cells, which would have an impact on viral replication. According to the ADMET profile and drug likeness prediction, each of the top 5 compounds is safe and possesses drug-like qualities. Conclusion: The current investigation identifies 5 phytocompounds in total as having the strongest binding affinities and potential inhibitory effects on HIV-1 Integrase activity
Keywords: AIDS; CD4+ T cell; Calophyllum lanigerum; HIV-1; HIV-1 Integrase; Viral replication